Comorbidities in Spondyloarthritis - Moltó, Anna; Nikiphorou, Elena (Frontiers in Medicine, 2018)
Comorbidities in Spondyloarthritis (SpA) add to the burden of disease by contributing to disease activity, functional and work disability and mortality. Thus, awareness of comorbidities in SpA is crucial in order to improve their screening and management and to ultimately improve outcomes in those affected. Osteoporosis has been reported to be the most prevalent comorbidity in SpA, and its risk is increased in these patients, compared to the general population; the risk of vertebral fractures requires further evaluation. Cardiovascular risk is also increased in this population, both due to an increase of the traditional cardiovascular risk factors in these patients, but also due to the presence of inflammation. The role of non-steroidal anti-inflammatory drugs (NSAIDs) in this increased risk needs further elucidation, but there is consensus on the need to encourage smoking cessation and to perform periodic evaluation of cardiovascular risk in these patients, particularly in the case of change in treatment course. Concerning the risk of cancer, no increased risk inherent to SpA seems to exist. However, an increased neoplastic risk can occur due to SpA treatments, e.g. P-UVA. Data is sparse on the risk of infections compared to RA, but there appears to be no risk in the absence of TNF-inhibitor exposure. Regardless of which comorbidity, a gap exists between recommendations for their management and actual implementation in clinical practice, suggesting that there is still a need for improvement in this area. Systematic screening for these comorbidities should improve both short and long-term outcomes in SpA patients.